High performance liquid chromatography-quantitative nuclear magnetic resonance (HPLC-qNMR) with a two-signal suppression method for purity assessment of avermectin B1a. Issue 22 (23rd May 2016) - Huang, Ting; Zhang, Wei; Dai, Xinhua; Li, Na; Huang, Liang; Quan, Can; Li, Hongmei; Yang, Yi
Abstract : HPLC-qNMR is a technology with great potential, which combines the high separation capability of HPLC and the high qualitative/quantitative analysis capability of NMR. Abstract : HPLC-qNMR (high performance liquid chromatography-quantitative nuclear magnetic resonance) is a technology with great potential, which combines the high separation capability of HPLC and the high qualitative/quantitative analysis capability of NMR. It overcomes the problem of overestimation in qNMR and the problem of unavailable reference materials in HPLC. But its current application is narrow due to the lack of a good method to eliminate the vast amount of signals from the protons of the mobile phase. This study proposed a new HPLC-qNMR method for a natural complex pesticide (avermectin B1a). Common solvents (CH3 CN and H2 O = 70 : 30) are introduced as the HPLC mobile phase, which reduces the cost to make its wider application possible. The solution mixture of the sample and the internal standard (benzoic acid) was separated by HPLC. Only the eluent of the target analyte (avermectin B1a) and the eluent of the internal standard were collected in one vial, and then were determined by qNMR with a new signal suppression method to suppress two signals from CH3 CN and H2 O simultaneously. After the optimization of key parameters for qNMR, the mean and uncertainty (94.63% ± 1.97%) is consistent with that from the mass balance method based on many instruments (93.70% ± 0.46%). The bias is no more than 1%. This method can be widely applied in the future due to its efficient separation capability, high qualitative/quantitative capability, very low cost, rapid operation and good accuracy.